Molecular epidemiology of enteric protozoa and genotyping of Blastocystis from porcine on the west coast of Peninsular Malaysia - Kalaiselvam, Ruviniyia (2017)
Enteric protozoa of animals are of a major public health concern as a number are known to be zoonotic with high rates of transmission via contaminated food and water. Pigs are known to be the reservoirs for many zoonotic pathogens worldwide that exert negative impacts to human health and the agricultural economy of many countries. The present study aims at determining the molecular prevalence and risk factors associated with enteric protozoa infection in pigs reared on farms located along the west coast of Peninsular Malaysia, and to genetically characterized and determine the diversity of Blastocystis subtypes that are infecting these pigs in the country. Fecal samples were collected from 450 pigs from 15 different farms along the west coast of Peninsular Malaysia, and subjected to nested PCR amplification using genus specific primers. Molecular detection revealed that pigs in the country harbored a relatively high prevalence of Balantidium (70.4%), Blastocystis (55.6%), Enterocytozoon (40.7%), Giardia (22.0%) and Cryptosporidium (19.3%). A total of 94.2% of the pigs examined were infected with one or more of these enteric protozoa. The highest protozoa co-infection was triple co-infection (37.0%), followed by quadruple coinfection (29.0%). Multiple logistic regression showed that the age of the farm and distance of farm from human settlement were significant risk factors associated with Giardia infection. The age of the farm and number of swine on the farms were significantly associated with Blastocystis infection. The multivariate model also showed that the age of pigs and the distance of the farms from human settlement were significant risk factors for Balantidium and Enterocytozoon infection. In addition, the farm production type also played a significant role in the prevalence of the latter. None of the epidemiological factors examined were significantly associated with Cryptosporidium infection. Positive amplicons of Blastocystis were cloned and sequenced to determine the genetic variability of the local Blastocystis isolates. Bioinformatics and phylogenetic analysis revealed the presence of four subtypes (ST1, ST3, ST5 and ST10) among the infected swine, of which ST1, ST3 and ST5 are known to be able to infect humans. The highest prevalence was with ST5 (66.7%), followed by ST10 (24.4%), ST3 (15.6%) and lastly ST1 (8.9%). Analysis of haplotype diversity and prevalence revealed that H029 and H061 of the ST5 group were the most common haplotypes in the pigs. The present study constitutes the first attempt to determine the molecular epidemiology of porcine enteric protozoa in the country, and the genetic composition of Blastocystis among swine in Malaysia. It is envisaged that the data obtained from this study will afford a clearer understanding on the epidemiology and genetics of zoonotic enteric protozoa infecting swine in the country, which in turn may facilitate country-wide efforts in the control and prevention of these zoonotic pathogens.